Characterizing modal behavior of a cantilever beam at different heating rates for isothermal conditions - Kamei, Khangamlung; Khan, Muhammad A.; Khan, Kamran A. (MDPI, 2021)
The effect of temperature on structural response is a concern in engineering applications. The literature has highlighted that applied temperature loads change the system vibration behaviour. However, there is limited information available about temperature impacting the dynamic response. This paper investigated the heating rates effects on modal parameters for both with crack and without crack conditions in a cantilever beam. A beam subjected to three heating rates was considered: 2, 5, and 8 °C/min. The first one was assumed as a slow heating rate while the others were assumed as moderate and high, respectively. This controlled rate of heating was achieved by using a proportional-integral-derivative (PID) temperature controller. The results showed that heating at different rates has little impact on modal parameters. While this effect is minimal at lower temperatures and more evident at higher temperatures. The results of temperature ramped at 2, 5, and 8 °C/min were compared with the numerical and analytical results only for all the isothermal conditions. It was observed that the beam natural frequency and its modal amplitude decrease with the increase in temperatures and crack depths. Therefore, it is concluded that the rate of heating can make a slight impact on the dynamics response of any mechanical system.
Keywords: fracture mechanics; modal response; vibration testing; vibration analysis; thermal distribution